Classification of Potential Risk Factors through HIRARC Method in Assessing Indoor Environment of Museums - Mohd Dzulkifli, Syahrun Neizam; Abdullah, Abd Halid; Yong, Lee Yee; Suhaimi Shamsuri, Mohd Mahathir (International Journal of Integrated Engineering, 2018)
Museums were established in Malaysia more than hundred years ago. Since the year 2005, Malaysia has been moving away from constructing new buildings in favor of refurbishing historic and old ones. A healthy environment at the museum building has been identified as one of the important element that must been considered. Here, IAQ has become an important factor to provide a healthy environment in the museum building, but it is not sure either IAQ in the museum building provide a good air quality or not. Â So, the purpose of this study was conducted to determine the potential risk factor of the museum building by using the Potential Risk Categories, as a tool to identify the suitable location to conduct the indoor environment assessment at the museum building. Based on four mains criteria in the Potential Risk Categories, it is found that, out of 24 museum buildings, there were 8 museum buildings has been identified as a medium potential risk while 16 museum buildings are low potential risk. So, the selection of location based on Potential Risk Categories is important for the next step of indoor environment assessment at museum building, so that the most critical risk museum building could be assessed and suggestion could be provided to minimize the potential risk available in the museum building.